Analisis Penerapan Tax Amnesty Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak Kendaraan Bermotor Dan Penerimaan Pajak Kendaraan Bermotor Di Samsat Kota Padang - Rumpi Rumbewas; Ingra Sovita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Tax amnesty is a step taken by the West Sumatra government to help taxpayers after the Covid-19 pandemic by providing tax relief in the form of a motor vehicle tax reduction program. Apart from that, the issuance of this policy is one of the ways taken to solve the problem of the decreasing number of payments and receipts of motor vehicle tax revenue in SAMSAT Padang City. This research uses a qualitative method with a descriptive approach to describe the findings obtained. This research aims to determine whether the implementation of the tax amnesty program can increase taxpayer compliance in paying motor vehicle tax, to determine whether the tax amnesty program is effective in increasing motor vehicle tax revenue, and to determine the factors that are obstacles in implementing tax amnesty in SAMSAT City Padang. The results of the research show that the implementation of the tax amnesty program to reduce motor vehicle tax has had a positive impact in increasing motor vehicle taxpayer compliance in paying motor vehicle tax at SAMSAT Padang City. The effectiveness of implementing the tax amnesty program to reduce motor vehicle taxes at SAMSAT Padang City in 2022 has been very effective compared to previous years with a percentage value of 107.13%. The existence of obstacles in implementing the tax amnesty program is not a big obstacle in tax services because additional SAMSAT outlets are also provided to make it easier for motor vehicle taxpayers to pay their motor vehicle tax. And the tax amnesty was implemented by the government as a solution to the obstacles that exist among society